2013
DOI: 10.3168/jds.2013-7121
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2 electronic cowside tests to detect subclinical ketosis in dairy cows and the influence of the temperature and type of blood sample on the test results

Abstract: The objective of this study was to determine the suitability of 2 electronic hand-held devices [FreeStyle Precision (FSP), Abbott GmbH & Co. KG, Wiesbaden, Germany and GlucoMen LX Plus (GLX), A. Menarini GmbH, Vienna, Austria] for measuring β-hydroxybutyrate (BHBA) in dairy cows. Three experiments were conducted to evaluate (1) the diagnostic performance of the devices, (2) the effect of the type of blood sample, and (3) the influence of the ambient temperature on the determined results. A total of 415 blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
75
8
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 29 publications
9
75
8
4
Order By: Relevance
“…To our knowledge, this is the first study comparing FreeStyle Optium and KetoVet systems for the measurement of BHB in dairy cattle. The correlation coefficient (r= 0.96) and the average difference (-0.01 mmol/L) between the standard method and the FSO were similar to those reported by Iwersen et al (2013) using the FSO System who founded r= 0.94 and average difference of +0.04 mmol/L and those reported by Voyvoda and Erdogan (2010) using the FSO system who reported r= 0.97 and average difference of +0.03 mmol/L. Iwersen et al (2009) evaluating the Precision Xtra meter system, which uses the same technique of the two devices used in our study, found a correlation coefficient of r= 0.95 and average difference of -0,03 mmol/L.…”
supporting
confidence: 71%
See 3 more Smart Citations
“…To our knowledge, this is the first study comparing FreeStyle Optium and KetoVet systems for the measurement of BHB in dairy cattle. The correlation coefficient (r= 0.96) and the average difference (-0.01 mmol/L) between the standard method and the FSO were similar to those reported by Iwersen et al (2013) using the FSO System who founded r= 0.94 and average difference of +0.04 mmol/L and those reported by Voyvoda and Erdogan (2010) using the FSO system who reported r= 0.97 and average difference of +0.03 mmol/L. Iwersen et al (2009) evaluating the Precision Xtra meter system, which uses the same technique of the two devices used in our study, found a correlation coefficient of r= 0.95 and average difference of -0,03 mmol/L.…”
supporting
confidence: 71%
“…Iwersen et al (2009) evaluating the Precision Xtra meter system, which uses the same technique of the two devices used in our study, found a correlation coefficient of r= 0.95 and average difference of -0,03 mmol/L. While in the study of Iwersen et al (2009), the Precision Xtra system underestimated the laboratory values of BHB, the work of Iwersen et al (2013) and Voyvoda and Erdogan (2010) overestimated data of BHB using the Precision Xtra meter and FSO systems, respectively. In our study, the average difference obtained by FSO system (-0.01 mmol/L) was very close to the laboratory BHB values.…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…The concentrations of BHBA used in this study were chosen according to the BHBA concentrations in cow serum [23]. Stock BHBA solution was prepared as follows: 1.206 g of BHBA powder was dissolved in 50 mL of distilled water, sterilized by filtration to obtain a concentration of 0.2 mM, and stored at -20°C.…”
Section: Methodsmentioning
confidence: 99%